Microtus mystacinus - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
177. East European Vole Microtus mystacinus French: Campagnol de De Filippi / German: Ostfeldmaus / Spanish: Topillo europeo oriental Other common names: Russian Vole, Sibling Vole, Southern Vole Taxonomy. Arvicola mystacinus De Filippi, 1865, Lar Valley, N Iran. Microtus mystacinus is in subgenus Microtus and mystacinus species group. It was recognized in 1972 as a distinct species from M. arvalis and subsequently reported under five different names: subarvalis named by M. N. Meyer, V. N. Orlov and E. D. Skholl’ in 1972 (not subarvalis by E. Heller in 1933), epiroticus, rossiaemeridionalis, levis, and mystacinus. It was separated from arvalis based on chromosomal evidence (2n = 54 in mystacinus and 2n = 46 in arvalis) and cross-breeding experiments. The latter failed to produce litters between mystacinus and arvalis. Taxonomic status of mystacinus is also evident from nucleotide sequences. Subspecific taxonomy was never thoroughly assessed. Monotypic. Distribution. N & E Europe (S Finland, Baltic states, Belarus, Ukraine, Moldova, and W & SW Russia), Balkans (E Romania, S Serbia, Macedonia, Bulgaria, and Greece), Turkey, Armenia, NW & N Iran, W & N Kazakhstan, and Russia as far E as Tobol River in W Siberia. Introduced to Svalbard and Jan Mayen Is in the N Atlantic and to several scattered localities in Siberia, Olkhon I in Lake Baikal, and Khabarovsk Krai in Russian Far East. Descriptive notes. Head—body 102-130 mm, tail 33-55 mm; weight 21-58 g. Males are, on average, heavier than females; means for 90day-old individuals are 30-5 g for males and 25-6 g for females. Individuals are, on average, larger in the south than the north. The East European Vole is moderately large, with short, stout, and large head; blunt muzzle; moderately large eyes; and long ears that protrude above fur. Tail averages 37% of head-body length. Legs are short, with six (exceptionally five) plantar tubercles. Females have eight nipples, two pairs each of pectoral and inguinal. Fur is shaggy and moderately long. Back is ...